Plasma proteome changes associated with refractory cytopenia with multilineage dysplasia - Májek, Pavel; Riedelová, Zuzana; Suttnar, Jiří; Čermák, Jaroslav; Dyr, Jan Evangelista (Proteome science, 2011)
BACKGROUND: Refractory cytopenia with multilineage dysplasia (RCMD) is a subgroup of myelodysplastic syndrome (MDS), which belongs to oncohematological diseases, occurring particularly in elderly patients, and represents a heterogeneous group of bone marrow diseases. The goal of this study was to look for plasma proteins that changed quantitatively or qualitatively in RCMD patients. RESULTS: A total of 46 plasma samples were depleted, proteins were separated by 2D SDS-PAGE (pI 4-7), and proteomes were compared using Progenesis SameSpots statistical software. Proteins were identified by nanoLC-MS/MS. Sixty-one unique, significantly (p < 0.05, ANOVA) different spots were found; proteins in 59 spots were successfully identified and corresponded to 57 different proteins. Protein fragmentation was observed in several proteins: complement C4-A, complement C4-B, inter-alpha-trypsin inhibitor heavy chain H4, and endorepellin. CONCLUSIONS: This study describes proteins, which change quantitatively or qualitatively in RCMD patients, and represents the first report on significant alterations in C4-A and C4-B complement proteins and ITIH4 fragments in patients with MDS-RCMD.